ESTUDO QUALITATIVO DE SUCESSÃO DA FAUNA INCRUSTANTE SOBRE RECIFES ARTIFICIAIS EM ÁREA SOB INFLUÊNCIA DE USINA TERMOELÉTRICA EM PERNAMBUCO, BRASIL - Fernandes, Múcio Luiz Banja; Silva, Andréa Karla Pereira da; Ferreira, Gledson Fabiano de Araújo; Nery, Patrícia Paula Coelho Felipe; Chaves, Adilson de Castro; Magalhães, Joana Soares; Campos, José Deividy dos Santos; Oliveira, Priscila Lopes de Souza (Revista Nordestina de Zoologia, 2010)
The project studies for deployment of artificial reefs in coastal areas, with the influence of thermoelectric plant were installed in June 2007. On the occasion was planned analysis of the fouling fauna fundamentally necessary for the establishment of a community reef. The implantation of an artificial reef in the area of influence of the canal water abstraction Termope shall target of minimizing operating costs for maintenance of ducts for cooling water in the Thermoelectric Power Plant of Pernambuco (Termope). Moreover, this proposed Research and Development - R & D represents the first step to rebuilding of inventories of benthic fauna in the region and nektonic Port Suape. At this stage of the research surveys were carried out and monitoring the early stages of ecological succession of encrusting organisms in the region indicated that Suape filamentous algae as primary colonizers, being replaced by colonies of octocorals and hydrozoans. During the succession process, other groups of organisms such as bryozoans, barnacles and colonial ascidians recruited spaces available, but without having complete substitution of one group by another which proved that the coastal environment, an area rich and balanced, with conditions of immediate responses to the process of installation of artificial reefs as a means of environmental compensation for the region of Port and Industrial Complex Suape.